2021
DOI: 10.1038/s41598-021-03818-3
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Scheimpflug topography values to distinguish between normal eyes, ocular allergy, and keratoconus in children

Abstract: To identify and compare keratometric, corneal thickness, and elevation parameters and indices among healthy children, ocular allergy, and keratoconus using the OCULUS Pentacam Scheimpflug topography system. This study included healthy children, children with ocular allergy (OA) without keratoconus, and children with keratoconus (KC). The study design consisted of a prospective evaluation and review of medical records from a Brazilian ophthalmology department. The exclusion criteria were inability to undergo th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…25 Studies that presented normative values of healthy school children using the BAD in Brazil displayed a significant similarity in the main indices. 26,27 In children aged 9.72 ± 0.66 years, BAD D 0.78 ± 0.65, ART max 446.57 ± 81.20, and PPI avg 1.00 ± 0.14 were recorded, 26 while in 7–11-year-old children BAD D 0.80 ± 0.61, ART max 446.42 ± 75.23, and PPI avg 1.00 ± 0.13 were obtained. 27 Normative tomographic values in preschool children were presented by Hashem et al, but for the group of 3–6-year-old and the number of examinees was only 17.…”
Section: Badmentioning
confidence: 94%
See 2 more Smart Citations
“…25 Studies that presented normative values of healthy school children using the BAD in Brazil displayed a significant similarity in the main indices. 26,27 In children aged 9.72 ± 0.66 years, BAD D 0.78 ± 0.65, ART max 446.57 ± 81.20, and PPI avg 1.00 ± 0.14 were recorded, 26 while in 7–11-year-old children BAD D 0.80 ± 0.61, ART max 446.42 ± 75.23, and PPI avg 1.00 ± 0.13 were obtained. 27 Normative tomographic values in preschool children were presented by Hashem et al, but for the group of 3–6-year-old and the number of examinees was only 17.…”
Section: Badmentioning
confidence: 94%
“…25 Studies that presented normative values of healthy school children using the BAD in Brazil displayed a significant similarity in the main indices. 26,27 In children aged 9.72 6 0.66 years, BAD D 0.78 6 0.65, ART max 446.57 6 81.20, and PPI avg 1.00 6 0.14 were recorded, 26 while in 7-11-year-old children BAD D 0.80 6 0.61, ART max 446.42 6 75.23, and PPI avg 1.00 6 0.13 were K1, the flattest radius of curvature of the cornea, D; K2, the steepest radius of curvature of the cornea, D; Kmax, point of the highest breaking strength (D); PTL, thickness of the thinnest location on the cornea (pachymetry thinnest location, mm); DATL, distance from the apex of the cornea to the thinnest location on the cornea (distance apex-thinnest location, mm); F. Ele. Th., elevation values for the thinnest point on the cornea for the front surface of the cornea in relation to the reference best-fit sphere (BFS) (mm); B. Ele.…”
Section: Badmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that approximately 50% of patients with unilateral involvement will have their other healthy eye eventually progress to KCN within the next few years with being at greater risk during the rst 6 years of onset [8] . KCN has no particular predominance over males or females [9] and has a general population prevalence estimated to be around 1 in 2000 but it varies depending on ethnicity, age, country of origin and the diagnostic criteria used [1,10] . For instance, in Denmark the prevalence of keratoconus has been reported to be as low as 4 whereas in the Middle East it was 22 per 100,000 persons [7] .…”
Section: Introductionmentioning
confidence: 99%